Continuous bilateral rectus sheath block as a rescue block following vertical midline laparotomy - Wong, Shee Ven; Ibrahim, Mohd Fauzi; Ismail, Che Ainun Nasihah; Mohamed Zaini, Mohamed Asri; Zainudin, Muhammad Zulhimi; Jamaludin, Najibah Zahirah; Abd Ghani, Muhamad Rasydan (Universiti Kebangsaan Malaysia, 2021)
Introduction: Peripheral nerve block has been adopted in many ERAS protocol as part of opioids-sparing-analgesia. Block failure is unavoidable in the hand of beginners and it presents great challenge as patients might be in severe pain, half-sedated, compromising optimal positioning for a rescue block. Besides, the concerns about local anaesthetic systemic toxicity (LAST) with subsequent local anesthetic (LA) injections is elevated. Post-operative anticoagulant prophylaxis therapy also complicates timing of intervention for neuraxial anaesthesia and deep regional blocks. Case description: We report a case of 33-year-old lady with Krukenberg tumour presented for a laparotomy TAHBSO. She underwent complicated operation with dense adhesion under general anaesthesia plus bilateral transversus-abdominis plane block after failed attempts of epidural catheter insertion. 4 hours postoperative, patient experienced breakthrough pain requiring rescue opioids. Considering the risk of LAST for a rescue block, patient was started on patient-controlled morphine bolus with background infusion, and it was subsequently converted to patient controlled fentanyl bolus with infusion in view of excessive sedation, nausea and ileus. Her opioids requirement remained high and hence on day-2 postoperatively, bilateral rectus sheath (BRSB) catheters were inserted for bolus dose of LA followed by continuous infusion. Her pain improved dramatically and opioids requirement was reduced to half. With better pain management, patient was then able to participate in physiotherapy and she started to ambulate and tolerate oral feeding on subsequent day. Fentanyl was off on day-4 and BRSB catheters were removed on day-6 without complications. Conclusion: BRSB may play a valuable role as a rescue block as it can be easily performed in supine position, requires smaller LA volume and appears safer compared to neuraxial or deep regional technique during the anticoagulant therapy. Its potential beyond analgesic adjunct for umbilical hernia repair or laparoscopic procedures worth further exploration.